The Role of Education in Social Mobility: A Systematic Literature Review of Structural and Cultural Barriers - Hikmat (Jurnal Abdimas Peradaban, 2024)
This article presents a systematic literature review that investigates the role of education in promoting social mobility while examining the structural and cultural barriers that hinder this process. Education has long been regarded as a critical pathway for individuals to improve their socioeconomic positions, yet its effectiveness is often constrained by unequal access and persistent cultural norms. By synthesizing findings from prior studies, this review identifies key structural obstacles, including economic disparities, limited educational resources, and policy shortcomings that perpetuate inequality. At the same time, it highlights cultural barriers such as gender roles, ethnic biases, and societal expectations that restrict individuals from fully benefiting from educational opportunities. The review employed a systematic search across major academic databases to ensure comprehensive coverage of relevant literature. A total of selected studies were analyzed based on predefined inclusion and exclusion criteria, enabling the extraction of thematic insights. The findings demonstrate that both structural and cultural dimensions interact in complex ways to shape educational outcomes and mobility trajectories. This article contributes to sociological discourse by offering a critical synthesis of existing research while identifying gaps for further investigation. The review underscores the necessity of holistic approaches that address both structural inequalities and cultural dynamics in order to enhance the transformative power of education in advancing social mobility.